The genus Manota Williston (Diptera, Mycetophilidae) in Japan, with a key to the Palaearctic species of the genus - Hippa, Heikki; Kjærandsen, Jostein; Saigusa, Toyohei (Zootaxa, 2011)
The Japanese fauna of Manota comprises of 11 out of 14 Palaearctic species with a strong influence of Oriental elements in the southern subtropical parts of the country. The following five new species are described: M. curvistylus, M. kyushuensis, M. omotoensis, M. tripectinata, and M. yaeyamaensis. Three species are recorded for first time from Japan: M. bilobata Papp, 2004, M. epigrata Hippa, 2009 and M. planilobata Hippa, 2008. The hypopygia of the Japanese specimens of M. bilobata and M. planilobata are illustrated. New Japanese records are given of the following three species: M. indahae Hippa & Kjaerandsen, 2010, M. satoyamanis Hippa & Kjaerandsen, 2010 and M. tunoae Hippa & Kjaerandsen, 2010. A key to the Palaearctic species of Manota is given.